Case report of Takotsubo syndrome following seizures in a patient with pyruvate carboxylase deficiency. Issue 3 (4th March 2021) - Sahdev, Nikhil; Oji, Onyedikachi; Babu, Aswin; Dutta Roy, Smita
Abstract: Background : Takotsubo syndrome (TS) is defined as transient left ventricular dysfunction, which is often related to an emotional or physically stressful event. We describe a case of TS in a lady with pyruvate carboxylase deficiency (PCD). Pyruvate carboxylase deficiency is rare condition with the majority of those affected demonstrating signs of failure to thrive, recurrent seizures, and metabolic acidosis. To our knowledge, this is the first documented case of TS in an individual with PCD. Case summary : This 28-year-old female presented to the emergency department after a tonic-clonic seizure. For 4 days prior to the presentation, she had been suffering from cough and pyrexia. On Day 2, she developed abdominal pain associated with tachycardia and hypotension, and an elevated troponin (791 ng/L). The echocardiogram showed a severely impaired left ventricular systolic function, regional wall motion abnormalities (RWMAs), and a visually estimated left ventricular ejection fraction of 25–30%. Eight days following admission her clinical state significantly improved, with a reduction troponin to 60 ng/L. A repeat echocardiogram on Day 9 showed complete resolution of cardiac function with no RWMAs. Following this, she was discharged from hospital the next day with a diagnosis of TS. Discussion : This is the first case report of TS in a patient with PCD. In this case, multiple aetiologies of TS such as emotional and physical stress, seizures, and acute infection were considered. This case also highlights that TS should be an important differential diagnosis in patients presenting with cardiac symptoms.